Art, outrage, dialogue: a McLuhan reading of three visual communicative practices in Cape Town public space - Brown, Storm Jade (Centre for Film and Media Studies, 2016)
This mini-dissertation places a specific focus on the City of Cape Town and considers the space between aesthetics, commercial interest and social relevance in public visual communication practices. Instead of making a general statement or providing a value judgement, this research examines the nature of the debate surrounding public artistic practices by referring to three main artists; namely Michael Elion, The Tokolos Stencil Collective and Freddy Sam. The basis of the discussion is centred around the recent controversy surrounding Michael Elion's Sea Point public art sculpture, Perceiving Freedom (2014) and the respective questions it raised about what public space means, who has the right to represent themselves, and what that looks like. By drawing a comparison with Perceiving Freedom (2014) to the visual communicative practices of Freddy Sam and The Tokolos Stencil Collective, this research examines the progression of the debate. This encompasses the ways in which each artist and their work serve to illuminate the different visual modes of engagement in Cape Town's public spaces. Due to the contemporary nature of the subject matter, this debate is engaged with on three different levels. The first level examines the context of this debate and each artist, whereas the second level considers the points where their respective visual communicative practices intersect and engage in dialogue with each other as well as the general public. The last level considers an alternative way of reading the content, context and form of visual communicative practices so that their resulting effect can be better understood. This is done with the use of Marshall McLuhan's (1964) total effect media theory. Although several other prominent South African artists are mentioned in the scope of this research, it is important to note that the focus still pertains to the aforementioned themes of aesthetics, commercial interest and social relevance in public visual representative practices. Therefore Michael Elion, The Tokolos Stencil Collective and Freddy Sam remain the specific focus of discussion, as their respective works are used to illustrate these three themes. The first level of engagement offers a theoretical background to the reader by briefly familiarising them with international street art and graffiti practices. This brief yet concise background allows for a better understanding of the history and politics surrounding unsanctioned public visual practices and how they differ to formal sanctioned and funded ones.